A low-cost web-based smart street lighting geographical information system for smaller towns and villages - Pružinec Filip; Mego Peter; Đuračiová Renata (Open Computer Science, 2020)
The use of LED lights in smart street lighting to save energy is efficient and very common in many developed cities. However, such a system results in higher initial costs, which may discourage smaller towns and villages from its purchasing. This paper therefore deals with the design and development of a smart street lighting control system for smaller cities and villages. Such a system is required to be economical from the perspective of development and production. Considering other requirements such as platform independence, high availability and broad support, we proposed to build a system as a web application using a custom light control service component. The result is a web application that consists of a user interface served by a web server and an application server used to communicate with light control service. In addition, the system is designed as a geographical information system to be easy to use for managing street lights in groups or individually, while displaying them on the map. The system allows automatic sensor-based light intensity modulation by default with the possibility of manual adjustment or override of the illumination. It also includes a device error notification system with a tool to navigate faulty devices. The presented system is a low-cost solution for intelligent street lighting control designed for smaller cities or villages. They can apply the designed architecture of the system and the specific technologies suitable because of their low-cost implementation.